(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The bicentennial of the Monroe Doctrine in December 2023 marks a pivotal moment in history, calling historians to engage in a renewed examination of inter-American relations. This article seeks to contribute to this important scholarly dialogue by offering a focused review of key works on US-Latin American cultural relations. Specifically, it examines scholarship that challenged entrenched cultural paradigms, particularly those interpretations of US-Latin American interactions that highlight asymmetry and potential hegemony. These interpretations are often traced, at least normatively, to the origins of the Monroe Doctrine. The review covers seminal books published from the late 1990s to the present.